Luther et le luthéranisme dans l’Encyclopédie - Cernuschi, Alain (2017)
Dans l’Encyclopédie(1751-1765) éditée par Diderot et d’Alembert, 165 articles évoquent Luther et le luthéranisme, de façon centrale ou plus marginale. Cet ensemble, disparate et polyphonique, est polarisé par l’opposition entre deux points de vue sur le Réformateur et son action : la charge polémique de l’orthodoxie catholique, étonnamment présente ; la distance critique mais tolérante de l’analyse philosophique des Lumières.
Diderot and D’Alembert’s Encyclopédie(1751-1765) includes 165 articles that evoke Luther and Lutheranism either centrally or in a more marginal way. The disparate and polyphonic whole is polarized by two opposingpoints of view on the Reformer and his activity: the polemical thrust of Catholic orthodoxy, which is surprisingly present; and the critical albeit tolerant distance of Enlightenment philosophical analysis.
Diderot and D’Alembert’s Encyclopédie(1751-1765) includes 165 articles that evoke Luther and Lutheranism either centrally or in a more marginal way. The disparate and polyphonic whole is polarized by two opposingpoints of view on the Reformer and his activity: the polemical thrust of Catholic orthodoxy, which is surprisingly present; and the critical albeit tolerant distance of Enlightenment philosophical analysis.
Diderot and D’Alembert’s Encyclopédie (1751-1765) includes 165 articles that evoke Luther and Lutheranism either centrally or in a more marginal way. The disparate and polyphonic whole is polarized by two opposingpoints of view on the Reformer and his activity: the polemical thrust of Catholic orthodoxy, which is surprisingly present; and the critical albeit tolerant distance of Enlightenment philosophical analysis.
Keywords: d’Alembert; Diderot; Jaucourt; Mallet; compilation; Tolérance; Polémique; Lumières; Encyclopédie